(untitled) (CIPEEX, 2022)
INTRODUCTION: CONSIDERED A PUBLIC HEALTH PROBLEM, DIABETES MELLITUS (DM) IS CHARACTERIZED BY METABOLIC, VASCULAR OR NEUROPATHIC ALTERATIONS, HAS A CHRONIC DEGENERATIVE CHARACTER AND IS ASSOCIATED WITH INSULIN DEFICIT, DM GROWS ON A LARGE SCALE AT A GLOBAL LEVEL (ANTƑO ET AL AL., 2013). OBJECTIVE: THE GENERAL OBJECTIVE OF THIS STUDY IS TO DESCRIBE HOW THE SCIENTIFIC LITERATURE POINTS TO THE HEALTH CARE OF DIABETIC PATIENTS. METHODOLOGY: THIS IS A BIBLIOGRAPHICAL WORK, WITH AN INTEGRATIVE REVIEW OF THE LITERATURE (MENDES; SILVEIRA; GALVƑO, 2008), WITH RESEARCH ON SCIENTIFIC ARTICLES AVAILABLE IN THE VIRTUAL HEALTH LIBRARY (VHL) AND SCIENTIFIC ELETRONIC LIBRARY ONLINE (SCIELLO). DATA: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS), NATIONAL LIBRALY OF MEDICINE (MEDLINE), NURSING DATABASE (BDENF), USING THE FOLLOWING DESCRIPTORS: DIABETES, SUS, HEALTH EDUCATION, NURSING EDUCATION , FAMILY HEALTH STRATEGY. RESULTS: AFTER READING AND INTERPRETING THE DATA THE CATEGORIES WERE REACHED: CATEGORY 1 - ATTENTION TO THE HEALTH OF THE DIABETIC; CATEGORY 2 - ATTENDANCE OF THE MULTIDISCIPLINARY TEAM; CATEGORY 3 - THE NURSE IN FRONT OF THE DIABETIC PATIENT. CORRECT CLASSIFICATION OF THE TYPE OF DM IS FUNDAMENTAL, BECAUSE THE CORRECT TREATMENT STARTS EARLIER AND HAS A GREATER POSSIBILITY OF SUCCESS, ANOTHER IMPORTANT MECHANISM IS THE EDUCATION ACTIVITIES AIMED AT DIABETIC PATIENTS. THE NURSE MUST PERFORM ALL THE PROCEDURES THAT THE PROTOCOL REQUIRES, FOR GREATER EFFECTIVENESS IN THE TREATMENT. CONCLUSION: DM IS A PUBLIC HEALTH PROBLEM AND IT IS EXTREMELY IMPORTANT THE PATIENT’S ADHERENCE TO TREATMENT AND THE CHANGE IN THEIR DAILY HABITS, BOTH IN FOOD AND IN THE PRACTICE OF PHYSICAL ACTIVITIES, WHICH TOGETHER WITH THE ACTION OF THE NURSES WILL CAUSE PATIENTS REACH NORMAL OR NEAR NORMAL LEVELS OF BLOOD GLUCOSE, THUS PROMOTING BETTER HEALTH.